(untitled) (Scientific journal of the Fergana State University, 2023)
There are many types of concepts defined in the scientific literature, but there is no generally accepted classification that allows us to imagine how the relationship between different types of artistic concepts is built, to determine how and what operational units of thinking interact. Within the framework of this article, approaches to the typology of concepts are considered; types of concepts according to their semantic content; specific features of national, cultural and artistic concepts, etc.